2015
DOI: 10.5005/jp-journals-10024-1633
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cariogenic Potential of Flavored Milk: An Experimental Study using Rat Model

Abstract: Objective: The purpose of this study was to evaluate and to compare the cariogenic potential of different commonly consumed flavored milk on caries development in rat's molar teeth. Materials and methods:Sixty Sprague-Dawley rats infected with an active growing culture of Streptococcus mutans were offered chocolate flavored milk, strawberry flavored milk, banana flavored milk, plain milk, sweetened plain milk with 5% sucrose, and 10% sucrose ad libitum.Results: Rats consuming flavored milk developed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(40 reference statements)
0
2
1
Order By: Relevance
“…Interestingly, the observed association between flavored milk and dental caries in this study could be a result of evolving trends in milk consumption practices in Saudi Arabia. Although prior observational studies [ 55 , 56 ] contrast our findings, a moderate cariogenic potential of flavored milk observed in a recent animal experiment and the possibility of developing nations adopting this new trend warrant further evaluation [ 57 ]. Incidentally, our study contributed towards ever increasing evidence for the association between dental caries and sodas (or soft drinks) [ 58 60 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Interestingly, the observed association between flavored milk and dental caries in this study could be a result of evolving trends in milk consumption practices in Saudi Arabia. Although prior observational studies [ 55 , 56 ] contrast our findings, a moderate cariogenic potential of flavored milk observed in a recent animal experiment and the possibility of developing nations adopting this new trend warrant further evaluation [ 57 ]. Incidentally, our study contributed towards ever increasing evidence for the association between dental caries and sodas (or soft drinks) [ 58 60 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Children with ECC consumed more flavoured milk compared with children of the caries‐free group, which could have contributed to their caries status. Studies using animal models have shown that adding a small amount of sugar to milk increases its cariogenicity . Milk with 5% sucrose, which is a typical sucrose concentration in flavoured milk, increases acid production in plaque .…”
Section: Discussionmentioning
confidence: 99%
“…This study found that a high consumption of milk may have detrimental effects on oral health, leading to higher caries experience. The previous study’s findings indicated that milk with added 5% sucrose demonstrated a moderate cariogenic potential and it was recommended that occasional consumption of sweetened milk as a beverage should be approached with caution despite its nutritional benefits [ 22 ]. The consumption of sugar-sweetened beverages was identified as the one of the most significant factors associated with dental caries [ 23 ].…”
Section: Discussionmentioning
confidence: 99%